Exogenous 6-benzylaminopurine enhances waterlogging and shading tolerance after anthesis by improving grain starch accumulation and grain filling - Zhang, Wenjing; Wang, Beibei; Zhang, Anmin; Zhou, Qirui; Li, Yang; Li, Lingyu; Ma, Shangyu; Fan, Yonghui; Huang, Zhenglai (Frontiers in Plant Science, 2022)
Due to the frequent occurrence of extreme weather events, the area of wheat affected by continuous cloudy rainfall is increasing, with waterlogging becoming a major limiting factor of wheat yield. To alleviate the effect, spraying exogenous plant growth regulators is often used. In this study, two wheat cultivars, waterlogging-tolerant Yangmai 18 and waterlogging-sensitive Sumai 188, were selected for waterlogging and shading (WS) after anthesis for 7, 11, and 15 days respectively. Three concentrations of 6-benzylaminoadenine (6-BA) solution (15, 25, and 35 mg·L−1) were sprayed after WS treatment and water was sprayed as the control. Then, the effect of spraying 6-BA on photosynthetic characteristics, starch content, grain filling characteristics, and yield was explored under artificially stimulated continuous cloudy rainfall during anthesis. Compared with the control, the application of 6-BA caused a significant increase in grain plumpness throughout grain filling, as well as increases in the net photosynthetic rate (Pn), stomatal conductance (Gs), and transpiration rate (Tr), and a significant decrease in the intercellular CO2 concentration (Ci) of the flag leaves, all of which enhanced the photosynthetic capacity. The content of total starch, amylose, and amylopectin in the grains also increased significantly compared with the control. After WS for 15 days, the starch content increased by 3.81%–11.41% compared with the control. Spraying 6-BA also prolonged grain filling, increased the average grain filling rate, and significantly increased the 1000-grain weight and yield. The thousand-grain weight increased by 5.06%–43.28%, and wheat yield increased by 8.93%–64.27% after spraying 25 mg·L−1 of the 6-BA solution. These findings suggest that the application of 6-BA after WS stress could significantly improve the photosynthetic performance, which is propitious to the accumulation and transport of photosynthetic products after anthesis. Besides, spraying 6-BA can also increase the duration and rate of grain filling and starch accumulation content and improve grain weight, thereby alleviating the adverse effects of WS on wheat yield. Overall, spraying 25 mg·L−1 of the 6-BA solution had an optimal effect. These findings provide a theoretical basis for the exploration of cultivation techniques and measures aimed at alleviating damage caused by continuous rainfall during wheat anthesis.